2015
DOI: 10.1108/jmp-10-2011-0090
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of transformational leadership and the work-family relationship

Abstract: Structured AbstractPurpose: The purpose of the study is to examine the ways in which leaders influence follower's work-life management. Specifically, we propose that personal (positive affect), social (managerial support for work-family balance), and job (autonomy) resources mediate the relationships between transformational leadership and work-family conflict and enrichment.Design/methodology/approach: The sample included 411 managers in 37 hotel properties across the United States. Findings:The relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 66 publications
(131 reference statements)
4
62
0
16
Order By: Relevance
“…An interesting question remains: How can one facilitate teacher autonomous behaviour? Transformational leadership has been found to be an important condition for autonomy of employees in other professional occupations (Hetland et al, 2011;Hammond et al, 2015). Therefore, we tested the extent that transformational leadership facilitates all four dimensions of teacher autonomous behaviour.…”
Section: Transformational Leadership Facilitates Teacher Autonomous Bmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting question remains: How can one facilitate teacher autonomous behaviour? Transformational leadership has been found to be an important condition for autonomy of employees in other professional occupations (Hetland et al, 2011;Hammond et al, 2015). Therefore, we tested the extent that transformational leadership facilitates all four dimensions of teacher autonomous behaviour.…”
Section: Transformational Leadership Facilitates Teacher Autonomous Bmentioning
confidence: 99%
“…Finally, it was investigated whether transformational leadership is an important condition to facilitate teacher autonomous behaviour. Previous studies found a significant relationship between these concepts in other professional occupations (Hetland et al ., ; Hammond et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Por esse motivo, a eficácia das políticas depende de um ambiente organizacional que apoie tais práticas (FIKSENBAUM, 2014). Como destacado por Hill et al (2008), deve haver uma relação de confiança entre empregador e empregado, além de uma cultura de apoio no trabalho.…”
Section: Discussionunclassified
“…O apoio gerencial também é um mediador significativo para o conflito trabalho-família (HAMMOND et al, 2015). A disponibilidade desses para ouvir e aconselhar os trabalhadores em problemas relacionados à dificuldade de equilibrar trabalho e família é fundamental para reduzir conflitos (FIKSENBAUM, 2014;AFRIANTY;BURGESS;ISSA, 2015), porque podem proporcionar a sensação de que a organização cuida e se preocupa com o bem-estar de seus empregados (MANSOUR; TREMBLAY, 2016), resultando em maior comprometimento afetivo (JANASZ et al, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation